MM millennium - Chancellor, Henry; De'ath, Emma; Pirie, Caroline Ross; Kidel, Mark ([S.l.] : CNN Productions [production company] ; Kuala Lumpur : Movie Magic [distributor], 1999)
A thousand years of history...in ten fasinating hours of programming
episode 1 The eleventh century : century of the sword - episode 2 The twelfth century : century of the axe - episode 3 The thirteenth century : century of the stirrup - episode 4 The fourteenth century : century of the scythe
Volume 1 - Episode 1-2, volume 2 - Episode 3-4 in
j.2 n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Executive producer, Sir Jeremy Isaac, Pat Mitchell ; series producer, Emma De'ath, Neil Cameron ; editor, Justin Amsden, Karin Steininger
Narrator:Ben Kingsley
Keywords: History, Ancient; World history